Impact muscle strength exercises in the development of some motor skills with the Cubs football - Saleh, Hamid; Hashim, Hasaneen (Journal of Physical Education, 2015)
Eating several specialists, researchers term fitness for the development of some motor skills of what falls under this term many qualities and physical and motor abilities. Given the importance of muscular strength in the various events and sporting activities through the use of resistors in a scientific and thoughtful to see the impact of some motor skills, but there are opinions launches caveats of using exercises muscle strength at the stage of age groups of cubs on it may cause adverse effects in the device structural (musculoskeletal). research objectives lies to prepare muscle strength exercises to develop the absolute power of the two men to the Cubs football players